دراسة تجريبية للتغيرات البعدية الناتجة عن عملية التقسية الكلية للمحاور الدليلية والجلب المستعملة بصناعة القوالب - قراجة, رولا (Latakia University Journal -Engineering Sciences Series, 2018)
تخضع معظم المكونات المستعملة بصناعة القوالب لمعالجات حرارية تتسبب بتشوهات شكلية وبعدية ما يستدعي التشغيل اللاحق. وحيث أن التشغيل المجدي (من وجهة نظر اقتصادية) يستدعي القدرة على التنبؤ المسبق بقيم التشوهات (بحيث يتم ترك علاوات تشغيل مناسبة خلال مراحل التشغيل السابق للمعالجة) ظهرت الحاجة لأعمال بحثية تسمح بالوصول للعلاقات القائمة بين متغيرات المعالجات الحرارية المعتمدة والتشوهات الموافقة الحاصلة على أشكال وأبعاد منتجات متعددة مصنعة من خلائط معدنية مختلفة. ضمن السياق أعلاه عالج البحث الحالي مشكلة التغيرات الحاصلة على القيم التصميمية للازواجات fits القائمة بين المحاور والجلب المستعملة بصناعة القوالب، حيث أن إخضاع تلك المنتجات للمعالجة الحرارية يتسبب بتشوهات متعددة ما يغير حالات الازواج من الوضع الانتقالي g6/H7 إلى وضع أخر مرتبط بمتغيرات المعالجة المطبقة و بأشكال وأبعاد ومعادن المكونات. الآلية التي اعتمدت خلال العمل قامت على قياس التغيرات البعدية الحاصلة على الأقطار المتوافقة لأزواج متعددة من المحاور والجلب المصنعة من فولاذ كربوني خليطة Ck45. تشير النتائج التي تم الحصول عليها إلى وجود علاقة وثيقة بين قيم متغيرات المعالجة المطبقة وبين التغيرات الحاصلة على طبيعة الازواجات القائمة بين المحاور والجلب. إضافة لذلك، تشير تلك النتائج لوجود قيم امثليه لمتغيرات المعالجة المطبقة بحيث أن الالتزام بها خلال المعالجة يؤدي للحد من التغيرات الحاصلة على طبيعة الازواجات القائمة. Components, which are used in moulding industry, are subjected to hardening heat treatment (HT) that causes dimensional variations (DVs), which require subsequent machining to be eliminated. Essentially, the need for the subsequent machining can be minimised (for economic reasons) if variables related to treatment process are perfectly adopted, something that needs recognised relations between HT variables and DVs. As the availability of such relations is limited to several individual cases, "that involve specific geometries and particular alloys", the need for further investigations that allow additional data to be generated was recognised. Within the above-mentioned context, the current work was initiated to address the problem of tolerance changes due to heat treatment of dowel pins and sleeves used in moulding industry. Since subjecting these products heat treatment causes multiple defects that alter cases of couples from the transitional situation g6 / H7 linked to the status variables treatment applied and the shapes and dimensions of the components and metals The technique adopted during the work was based on measuring the dimensional changes occurred of internal and external diameters of a set of compatible pairs of pins and sleeves manufacturer of Ck45 alloy. The obtained results point out to the presence of optimum values of the heat treatment variables, and indicate that the adoption of these values minimizes the DVs of the dowels and sleeves and eliminates the need for the subsequent machining in order to correct the resulted fits between these components.